The regulation of takeovers and mergers in Malaysia - Ambaras Khan, Mushera Bibi (2015)
The Code on Take-overs and Mergers 1998 was the first codified law on takeover and merger in Malaysia. The 1998 Code was heavily influenced by the English takeover law. Due to the tremendous development on takeovers and mergers exercise, the 1998 Code was revised and later replaced by the Malaysian Code on Take-overs and Mergers 2010, deriving its power from section 217 of the Capital Market and Services Act 2007 (CMSA). The key objectives of the Code are to strengthen investor protection, institute higher standards of governance in takeovers and mergers activities, enhance transparency and improve efficiency. Takeovers and mergers in Malaysia have largely been friendly in nature.